EVALUASI KINERJA PROGRAM KOTAKU (KOTA TANPA KUMUH) RIAU (Studi Kasus: Kelurahan Tirta Siak, Kecamatan Payung Sekaki, Pekanbaru, Riau) - Retno Eka Novita; Taufik Dwi Laksono; Rossy Armyn Machfudiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Tirta Siak Village is one of the Villages in Pekanbaru City that receives assistance from National Slump Upgrading Program (NSUP), because this Village has a slump area of 21,53%. In 2022 and 2023, NSUP has built waste bank, repaired roads and drainage, built artesian wells and water towers. This research aims to evaluate the performance and level of success of NSUP in Tirta Siak Village. This research uses a quantitative descriptive method by collecting observations in the field, interviews, questionners, and reviewing documents. The analyzes carried out are analysis of the effectiveness or achievements of NSUP, cost and benefit analysis, sensitivity analysis, analysis of satisfaction or response to NSUP, and analysis of the impact of NSUP. From the results of the analysis, it was found that the performance of NSUP obtained good results because the assesment of satisfaction or response to NSUP was very satisfied. The the succes rate of NSUP in Tirta Siak Village is successful, because from the results of the analysis of the effectiveness or achievements of NUSP it can be completed 100% according to plan. In the cost and benefit analysis, the BCR value was 1.3423 which shows that NSUP is feasible to implement. The results of the sensitivity analysis show that NSUP in Tirta Siak Village is quite vulnerable to increasing costs and decreasing benefits. Then, from the results of the impact analysis of NSUP, it was found that the A Syimp. Sig (2-Tailed) value was smaller than 0,05 which means that there was a difference between before and after NSUP was implemented.